PENGARUH IMPLEMENTASI IFRS DALAM INDEKS GRAY: LEVERAGE, LIKUIDITAS, PROFIBILITAS, PORSI SAHAM PABLIK TERHADAP PENGUNGKAPAN LAPORAN KEUANGAN - Inti Sari; M. Cholid Mawardi; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effect of IFRS implementation in the gray leverage index, liquidity, profitability, and the share of public shares on the disclosure of financial statements. The population in this study are manufacturing companies in the food industry sector which are listed on the Indonesia Stock Exchange in 2019-2021. This study uses quantitative research to retrieve secondary data sourced from the financial statements of manufacturing companies in the food industry sector listed on the Indonesia Stock Exchange (IDX). There are 18 companies that are sampled in this study. This study uses multiple regression analysis. The result of this research is that the gray leverage index, gray liquidity index, profitability gray index and gray index of public shares have an influence on the disclosure of financial statements. Partially, the gray leverage index variable has no effect on the disclosure of financial statements. The gray liquidity index variable has no effect on the disclosure of financial statements. Profitability gray index variable has no effect on financial statement disclosure. While partially the gray index variable, the portion of public shares has a positive effect on the disclosure of financial statements.Keywords: Gray Leverage Index, Liquidity Gray Index, Profitability Gray Index, Gray Index of Public Stock Portions and Financial Statements Disclosures